Elastic and 'transparent bone' as an electrochemical separator. (June 2019) - Owuor, P.S.; Inthong, S.; Sajadi, S.M.; Intawin, P.; Chipara, A.C.; Woellner, C.F.; Sayed, F.N.; Tsang, H.H.; Stender, A.; Vajtai, R.; Pengpat, K.; Eitssayeam, S.; et al.
Abstract: The organic matrix of a bone mainly composed of a collagen matrix serves as a crucial component for remarkable toughness and strength in bones. The porous collagen matrix can also serve as an efficient template for various applications such as nanoparticle synthesis, catalysis or catalysis supports, electrochemical separator, filtration membrane, and tissue engineering. However, fabricating collagen matrix from bones without degrading its morphological structure still remains a challenge. Here, we present evidence of how ceramic crystals from a bone can be removed to fabricate a complete 'transparent bone' structure with improved porosity and elasticity. We show that demineralization or selective etching using dilute acid (citric) can remove ceramic mineral nanoparticles without degrading the collagen matrix. The transparent bone collagen matrix is investigated as the separator in electrochemical supercapacitor with aqueous electrolyte where it shows better performance compared with conventional separators.